No detectable Weddell Sea Antarctic Bottom Water export during the Last and Penultimate Glacial Maximum - Huang Huang (Nature Portfolio, 2020)
The Southern Ocean plays a key role in glacial-interglacial transitions and today, Weddell Sea derived Antarctic Bottom Water is one of the most important deep water masses. New records show that in contrast to today, no Weddell Sea water was exported during the last two glacial maxima, providing new insights towards the condition of Antarctic Bottom Water formation in extreme climate states.